The Effect of Sustainability Reporting Disclosure and Liquidity on Company Value with Ownership Concentration Variables as Moderating - Zumratul Meini; Leily Chusnul Chotimah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The high and low stock prices indicate the level of success of the management of a company. Changes in stock prices will cause gains or losses that reflect the value of a company. This study aims to prove empirically the factors that can affect firm value, namely the disclosure of sustainability reporting and liquidity. The novelty of this research is to test whether the concentration of ownership can moderate the effect of sustainability reporting and liquidity on firm value. The data used in this study is panel data of 37 companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Data processing is done with WarpPLS 0.8. The results showed that the disclosure of sustainability reporting has no effect on firm value, while liquidity had a positive effect on firm value.